Analysis of The Effectiveness of Hotel Tax, Restaurant Tax, and Street Lighting Tax in Increasing Regional Tax Revenue of East Lombok Regency in 2018-2022 - Osalan, Lalu Ami; Alwi, Muhammad; Agustiana, Eka (The Es Accounting And Finance, 2024)
This study aims to analyze the effectiveness and contribution of hotel tax, restaurant tax, and street lighting tax in East Lombok Regency in 2018-2022. This study uses a quantitative research type. Data obtained from the Regional Revenue Agency of East Lombok Regency in 2023. The results of this study indicate that the effectiveness of hotel tax in 2018-2022 obtained an average of 42.44%, which falls into the ineffective criteria, the effectiveness of restaurant tax obtained an average of 99.87%, which falls into the effective criteria, and the effectiveness of street lighting tax obtained an average of 98.95%, which falls into the effective criteria, while the hotel tax contribution obtained an average of 0.95%, which falls into the very poor criteria, the restaurant tax contribution obtained an average of 7.35%, which falls into the very poor criteria, and the street lighting tax contribution obtained an average of 41.10%, which falls into the good criteria. The implications of this study explain that strict supervision of taxpayers should be carried out and re-registering taxpayers to ensure that all taxpayers have been registered and fulfill their tax obligations in order to significantly increase regional tax revenues.